Meta-Analysis Of Research Carried Out At Secondary Schools In Turkey - YILMAZ VİRLAN, AYŞE (My University, 2018)
Secondary education is the second stage traditionally found in formal education, beginning about age 11 to 13 and ending usually at age 15 to 18. The main difference between primary school and secondary school is the curricula and the organization of the courses and teachers. In other words, there is no class teacher any longer. It is the transition period and the expectations and readiness level of learners are questions that needs to be looked into. It is a very important level of education since it plays a key articulating role between primary schooling, tertiary education, and the labor market. The specific dynamics of this articulation is crucial because it determines future educational and job opportunities for young people. Secondary school is very important since today’s rapidly growing economies depend on the creation, acquisition, distribution, and use of knowledge, and this requires an educated and skilled population. In addition, there is growing evidence that perhaps half or even more of aggregate economic growth is driven by increases in factor productivity. Secondary education plays a particularly important role in this regard. In many countries there is an increased demand for workers with secondary schooling.
Keywords: Sosyal ve Beşeri Bilimler; Eğitim; Eğitim Bilimleri; Eğitim Programları ve Öğretim; Social Sciences and Humanities; Education; Educational Sciences; Curriculum Development and Teaching Methods; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities